Feeding tea polysaccharides affects lipid metabolism, antioxidant capacity and immunity of common carp (Cyprinus carpio L.) - Yang, Guokun; Liang, Xiaomin; Hu, Jihong; Li, Chengquan; Hu, Wenpan; Li, Keke; Chang, Xulu; Zhang, Yanmin; Zhang, Xindang; Shen, Yawei; Meng, Xiaolin (Frontiers in Immunology, 2022)
Tea polysaccharides plays a role in lipid metabolism, antioxidant capacity and immunity of mammals. To investigate the functions of tea polysaccharides on fish, the common carp (Cyprinus carpio L.) was selected as the animal model in this study. In our study, the common carp (45±0.71g) were randomly divided into four groups and were fed fodder with 50% carbohydrate. The common carp were orally administrated with 0 mg/kg BW (control group), 200 mg/kg BW (low-dose group), 400 mg/kg BW (medium-dose group) and 800 mg/kg BW (high-dose group) tea polysaccharide for two week. At the end of experiment, the glucose, TG and MDA contents in serum were significantly decreased by tea polysaccharides treatment. The serum activities of SOD were significantly increased by low-dose tea polysaccharides treatment. The serum activities of GPX were significantly increased by medium-dose tea polysaccharides treatment. The serum levels of IL-1β and TNFα were significantly decreased in the tea polysaccharides treatment group. In the high-dose treatment group, the serum level of TGFβ was significantly increased, and the serum level of IL-12 was markedly decreased. In the hepatopancreas, the expression of acc1, fas, srebp1c, lpl, gys and pparγ were significantly reduced, and the expression of pygl, cat, mnsod, ho-1 and gr were significantly up-regulated in the tea polysaccharides group. In the intestine, the expression of zo-1, occ and gip was significantly up-regulated in the high-dose treatment group. Moreover, the expression of glut2 and sglt1 were significantly down regulated. In the spleen, the expression of il-12, tnfα and il-6 were significantly decreased, and the expression of il-10 and tgfβ was significantly increased by the tea polysaccharides. In the spleen cells, the tea polysaccharides could relieve the LPS-induced immune damage. In conclusion, tea polysaccharides can improve antioxidant capacity, lipid metabolism and immunity of common carp.